Hydroclimate reconstruction during the last 1000 years inferred from the mineralogical and geochemical composition of a sediment core from Lake-Azuei (Haiti). (July 2023) - Noncent, David; Sifeddine, Abdelfettah; Emmanuel, Evens; Cormier, Marie-Helene; Briceño-Zuluaga, Francisco J; Mendez-Millan, Mercedes; Turcq, Bruno; Caquineau, Sandrine; Valdés, Jorge; Bernal, Juan Pablo; King, John W; Djouraev, Irina; et al.
This study aims to reconstruct the hydro-climatic variations over the last 1000 years in Haiti using mineralogical and geochemical composition of well dated lacustrine sediment core retrieved from Lake Azuei. The results show changes in sedimentological processes linked to environmental and climatic variations. The general pattern suggests a wetter Medieval Climate Anomaly (MCA), drier Little Ice Age (LIA), high climate variability during the MCA-LIA transition and more anthropogenic impacts that dominate natural climate during the Current Warm Period (CWP). The MCA period ( 1000–1100 CE) thus appears marked by increase sedimentation rate supported by higher terrigenous input linked to erosive events particularly increases in precipitation. During the LIA, particularly from 1450 to 1600 CE, there is a great variation toward a decrease of terrigenous input, which is related to a decrease on sedimentation rate and increase Mg-calcite precipitation, suggesting less precipitation and high evaporation respectively during dry climate conditions. The MCA-LIA transition ( 1200–1400 CE) is characterized by variations between terrigenous input, Mg-calcite formation and organic matter deposition, which indicate succession of dry and humid conditions. The CWP (1800–2000 CE) shows a progressive increase on sedimentation rate and decrease of gray level, which indicate more organic matter sedimentation as consequence of anthropogenic activities in the surrounding basin of the lake. High-resolution gray level analysis, which reflects principally variations in terrigenous input, carbonate mineral formation and organic matter deposition, shows that the AMO, NAO, PDO and ENSO are the principal modes affecting the hydro-climatic changes in Haiti during the last millennium. In addition, temporal correlation of other Caribbean paleoclimate records with our geochemical and mineralogical data, suggests that trends observed in Lake Azuei were controlled by regional climate, likely associated with shifts in the position of the ITCZ.